Systematic mapping studies on argumentative knowledge construction analysis frameworks towards improving students' higher order thinking skills - Ibrahim, S. N. K. A. (Institute of Electrical and Electronics Engineers Inc., 2016)
Computer-supported collaborative learning is one of the most promising innovations to improve teaching and learning with the help of modern information and communication technology. Constructing knowledge via online collaborative and social learning has been realized as one of the ways to nurture students' higher order thinking skills. In the collaborative environment, it normally involves processes of evidence and argumentation which is refers to making convincing claims backed up by assure evidence and broad understanding of various aspects of an issue. When dealing with argumentation, knowledge is shared or transmitted among learners as they work towards common learning goals, for example, a shared understanding of the subject at hand or a solution to a problem. Mainly, learners are not passive input receiver but are active in their process of knowledge acquisition as they participate in discussions, search for information, and exchange opinions with their peers. In collaborative argumentation, knowledge is constructed and shared among peers, not owned by one particular learner after obtaining it from the learning activities, course materials or instructor. However, how to analyze argumentative knowledge construction process in online collaborative learning to confirm that it is really reflects students' higher order thinking skills? Thus, the aim of this paper is to provide an overview of argumentative knowledge construction analysis frameworks and identifying gaps that merit future investigation. For this purpose, we conducted a systematic mapping study on the argumentative knowledge construction analysis frameworks to answer that question. The main results are summarized in this paper.